Humanizing the laws of war : the Red Cross and the development of international humanitarian law - Geiss, Robin; Zimmermann, Andreas; Haumer, Stefanie, 1978- (Cambridge : Cambridge University Press, 2017)
Over the past 150 years, the International Committee of the Red Cross (ICRC) has been one of the main drivers of progressive development in international humanitarian law, whilst assuming various roles in the humanization of the laws of war. With select contributions from international experts, this book critically assesses the ICRC's unique influence in international norm creation. It provides a detailed analysis of the workings of the International Red Cross, Red Crescent Movement and ICRC by addressing the milestone achievements as well as the failures, shortcomings and controversies over time. Crucially, the contributions highlight the lessons to be learnt for future challenges in the development of international humanitarian law. This book will be of particular interest to scholars and students of international law, but also to practitioners working in the field of international humanitarian law at both governmental and non-governmental organizations.
Introduction : the International Red Cross and Red Crescent movement and the development of international humanitarian law / Stefanie Haumer, Robin Geiss and Andreas Zimmermann -- The International Committee of the Red Cross and the Geneva Conventions of 1949 / Robert Heinsch -- The International Committee of the Red Cross and the additional protocols of 1977 / Michael Bothe -- The International Committee of the Red Cross and the clarification of customary international humanitarian law / Jean-Marie Henckaerts -- The International Committee of the Red Cross''interpretive guidance on the notion of direct participation in hostilities': see a little light / Robert Cryer -- Development of treaties limiting or prohibiting the use of certain weapons : the role of the International Committee of the Red Cross / Kathleen Lawand and Isabel Robinson -- Between'constructive engagement','collusion' and'critical distance' : the International Committee of the Red Cross and the development of international criminal law / Carsten Stahn -- The International Committee of the Red Cross : a unique actor in the field of international humanitarian law creation and progressive development / Robin Geiss and Andreas Zimmermann.
Title from publisher's bibliographic system (viewed on 07 Jul 2017).
Keywords: International Committee of the Red Cross -- Influence; Humanitarian law